Tapping into the Right-Brain: Using Visual Culture to Accelerate Early-Stage Adult Maltese Language Learning - Żammit, Jacqueline (International Journal of Language and Literary Studies, 2023)
Recent evidence suggests that right-brain practices play an important role in language learning. However, little is known about how visual culture can be used to stimulate these practices and increase language knowledge retention in adult second language learners. This study explores the role of right-brain processes through visual culture, focusing on teaching Maltese to international adults. The study conducts a focus group of twenty-seven teachers to investigate various visual culture practices used in language classes. The findings have significant implications for language researchers and teachers beyond the specific context of Maltese language learning. By highlighting the role of right-brain practices and their potential impact on language learning, this study offers pedagogical implications that extend to other language-learning contexts. It provides valuable recommendations for employing specific visual culture practices to facilitate language learning, including drawing, sketching, orthographic mapping, the memory palace approach, wordless picture books, picture-based learning methods, infographics, Face Memory Game, Spot the Difference, Word Search Puzzles, the Hidden Object Game, videos, the Shadow Matching, Find the Differences, and colour-coding methods. These recommendations can inform language researchers and teachers seeking to enhance learning outcomes through visual culture practices in various language learning contexts.